The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1091/mbc.e08-07-0671
|View full text |Cite
|
Sign up to set email alerts
|

The TP53INP2 Protein Is Required for Autophagy in Mammalian Cells

Abstract: Using a bioinformatic approach, we identified a TP53INP1-related gene encoding a protein with 30% identity with tumor protein 53-induced nuclear protein 1 (TP53INP1), which was named TP53INP2. TP53INP1 and TP53INP2 sequences were found in several species ranging from Homo sapiens to Drosophila melanogaster, but orthologues were found neither in earlier eukaryotes nor in prokaryotes. To gain insight into the function of the TP53INP2 protein, we carried out a yeast two-hybrid screening that showed that TP53INP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 41 publications
2
119
2
Order By: Relevance
“…Interestingly, tumor protein 53-induced nuclear protein 2 (TP53INP2) can translocate from the nucleus to the autophagosome structures and interact with LC3 and VMP1, following activation of autophagy by rapamycin or starvation. 59 It is unknown, however, whether Beclin 1 mediates interaction between TP53INP2 and LC3/VMP1.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…Interestingly, tumor protein 53-induced nuclear protein 2 (TP53INP2) can translocate from the nucleus to the autophagosome structures and interact with LC3 and VMP1, following activation of autophagy by rapamycin or starvation. 59 It is unknown, however, whether Beclin 1 mediates interaction between TP53INP2 and LC3/VMP1.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…52 Interestingly, TP53INP2 translocates from the nucleus to autophagosomes upon induction of autophagy, where it binds to LC3 and other LC3-family members (Gate-16, GABARAP), as well as VMP1. Therefore, TP53INP2 was proposed to act as a scaffold protein to recruit other Atg proteins to the IM.…”
Section: Ulk1 Andmentioning
confidence: 99%
“…TP53INP2 interacts with the pre-autophagosomal membrane protein VMP1 allowing the recruitment of LC3 to the autophagosome. 11 It was also shown that TP53INP2 regulates autophagy in Drosophila cells. 12 These findings led us to hypothesize that TP53INP1 also has a role in autophagy.…”
mentioning
confidence: 99%